PENTINGNYA DISIPLIN ROHANI BERDASARKAN SURAT 1 KORINTUS 9:24-27 - Dilla, Minggus (Sekolah Tinggi Teologi Arastamar Bengkulu, 2014)
A disciplined life is the hope of many people. But often humans fail to do it. Therefore it is important to pay attention to the important axis in human life. Namely how the spirituality. With a basis that spiritual discipline will produce disciplined people. Therefore through this article the Bible will contribute to a spiritually disciplined attitude to life.